PRIMARY PERICARDIAL LIPOSARCOMA IN A YOUNG LADY: Pericardial Liposarcoma - Lodhi, Dr Hamza Ali; Waqas, Muhammad; Jampana, Srinavasa; Aguilar, Santiago; Mushtaq, Asim; Farooq, Hina (Pakistan Armed Forces Medical Journal, 2018)
Liposarcomas are tumors that appear to arise from precursors of adipocytes and are most commonly found in theextremities and retroperitoneum. They can metastasize to pericardium, but a primary liposarcoma in pericardiumis very rare and generally has an insidious onset and often presents with complications. Treatment is primarilysurgical; doxorubicin has a limited role in treatment. Now newer receptor directed therapies have shown benefitin liposarcomas. Primary pericardial liposarcoma due to its rarity is best treated at a high volume center. Here wepresent to our colleagues a case of primary pericardial liposarcoma in a young lady; whom we referred to atertiary care center after diagnosis for optimum care.